Optimizing the Performance of Local Tour Guides: A Case Study of Meat Tourism Village, Toba District - Nainggolan, Hetty Claudia; Pakpahan, Rosdiana; Khairannur, Wilda (Jurnal Ilmiah Global Education, 2024)
This research discusses the development aimed at enhancing the technical competencies of Tour Guides in Meat Tourism Village. The research findings are outlined in several responses to the problem formulations, namely the technical competency conditions of local tour guides in Meat Tourism Village and the formulation of strategies to enhance the technical competencies of local tour guides in Meat Tourism Village. This research was conducted using descriptive analysis methods through interviews, observations, documentation, and literature review. Optimizing the role of local tour guides in Meat Tourism Village, Toba District, has a positive impact on tourism development, although not yet fully maximized, especially in the economic sector. The limited number of tourist visits to Meat necessitates improvements and evaluations of the tourism experience, as well as an understanding of tourism ethics. The optimization of the role of local tour guides in Meat Village not only contributes to the enhancement of knowledge and skills of the guides but also creates more satisfying tourism experiences for visitors. By designing diverse and appealing tour routes, tour guides are capable of presenting the holistic beauty of nature, history, culture, and local uniqueness. This provides opportunities to attract more tourists and enhance the destination's appeal.